Biodiesel CO2 emissions: A comparison with the main fuels in the Brazilian market - Coronado, Christian Rodriguez [UNESP]; de Carvalho, Joao Andrade [UNESP]; Silveira, Jose Luz [UNESP] (Elsevier B.V., 2009)
The use of biodiesel is increasing as an attractive fuel due to the depleting fossil fuel resources and environmental degradation. This paper presents results of an investigation on the potentials of biodiesel as an alternative fuel and main substitute of diesel oil, comparing the CO2 emissions of the main fuels in the Brazilian market with those of biodiesel, in pure form or blended in different proportions with diesel oil (2%, 5%, and 20%, called B2, B5, and B20, respectively). The results of the study are shown in ton CO2 per m(3) and ton CO2 per year of fuel. The fuels were analyzed considering their chemical composition, stoichiometric combustion parameters and mean consumption for a single vehicle. The fuels studied were: gasoline, diesel oil, anhydrous ethyl alcohol (anhydrous ethanol), and biodiesel from used frying oil and from soybean oil. For the case of biodiesel, its complete life cycle and the closed carbon cycle (photosynthesis) were considered. With data provided by the Brazilian Association of Automotive Vehicle Manufacturers (ANFAVEA) for the number of vehicles produced in Brazil, the emissions of CO2 for the national fleet in 2007 were obtained per type of fuel. With data provided by the Brazilian Department of Transit (DENATRAN) concerning the number of diesel vehicles in the last five years in Brazil, the total CO2 emissions and the percentage that they would decrease in the case of use of pure biodiesel, B100, or several mixtures, B2, B5 and B20, were calculated. Estimates of CO2 emissions for a future scenario considering the mixtures B5 and B20 are also included in this article. Crown Copyright (C) 2008 Published by Elsevier B.V. All rights reserved.
Keywords: Biodiesel; Emissions; Ethanol; Gasoline; Diesel; Combustion